Políticas públicas em agroecologia para os povos indígenas: um estudo de caso sobre o programa carteira indígena na baixada santista - Costa, Renata Maria Guerreiro Fontoura (Universidade Federal de São Carlos, 2012)
Public policies for indigenous peoples in Brazil have undergone several changes over the last two decades. After the end of military dictatorship and the return to democracy, it was started a process of diversification of indigenous policies, which occurred in conjunction with the process of decentralization of public policies in general. In this sense, policies toward the issue of extension and rural development are part of this process, which began to be reformed and to incorporate indigenous peoples as potential beneficiaries. Moreover, from the 70s of last century, the indigenous organization and the civil society began to participate in political arena. It transforms the political and social force hitherto in our country. The Carteira Indígena Program is the result of a partnership between the Ministry of Social Development and Ministry of the Environment, started in 2004 and its objective is the promotion of food security and sustainable development in the territories indigenous. The agroecology is indicated as one of its principles of operation. This study analyzes the decentralization process in public policies and the perceptions of social actors involved the implementation of the Carteira Indígena Program in terms of its benefits, difficulties and unanticipated results, though a case study carried out in two villages in the municipality of Santos. Many challenges have been listed by the stakeholders interviewed, including the discontinuity of actions, lack of technical support, community organization, among others. In this perspective, the Carteira Indígena Program, among other government programs, aims the sustainability in Indigenous communities and emerges as a development opportunity for these people. At the same time, many obstacles are noted during the implementation of those policies. This research shows that the coherence and integration of state action in the decentralization context faces a wide range of problems to reach the sustainable management in indigenous territories.
Public policies in agroecology for indigenous peoples: a case study about the carteira indígena program in the baixada santista
Keywords: Agroecologia; Políticas indigenistas; Comunidades indígenas; Políticas públicas - descentralização; Indigenous Policies; Agroecology; Indigenous Communities; Public Policies; Decentralization; CIENCIAS AGRARIAS